1991
DOI: 10.1034/j.1600-0889.1991.t01-1-00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variations of upper tropospheric and lower stratospheric carbon dioxide

Abstract: Systematic collection of air samples was made using commercial jet airliners between Tokyo, Japan and Anchorage, Alaska and between Tokyo and Sydney, Australia in 1984 and 1985. The amplitude of the seasonal CO2 cycle in the upper troposphere was found to be largest in high latitudes of the northern hemisphere but decreased and lagged in phase as the equator was approached. The cycle was still clearly observable in the southern hemisphere, due to southward transport of the northern hemispheric air through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
111
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(144 citation statements)
references
References 0 publications
32
111
1
Order By: Relevance
“…Plumb and Mahlman (1987) and Plumb and McConalogue (1988) pointed out that the tropical tropopause calculated by their transport parameters was too high. In fact, such a situation was also found to be the case in our own numerical experiments with CO2; when compared with the annual mean CO2 concentration obtained in the upper troposphere (Nakazawa et al, 1991), the model results showed higher values. To reduce the vertical transport, we decreased the vertical diffusion coefficients at 50 and 150hPa between 18N and 18S (P. P. Tans, private communication).…”
Section: Model Validationmentioning
confidence: 66%
See 1 more Smart Citation
“…Plumb and Mahlman (1987) and Plumb and McConalogue (1988) pointed out that the tropical tropopause calculated by their transport parameters was too high. In fact, such a situation was also found to be the case in our own numerical experiments with CO2; when compared with the annual mean CO2 concentration obtained in the upper troposphere (Nakazawa et al, 1991), the model results showed higher values. To reduce the vertical transport, we decreased the vertical diffusion coefficients at 50 and 150hPa between 18N and 18S (P. P. Tans, private communication).…”
Section: Model Validationmentioning
confidence: 66%
“…The concentration difference between the surface and 8 km is about 10 ppbv. The fact that the destruction of CH4 with OH is enhanced in the lower troposphere (Langenfelds et al, 1993) and that the northern hemispheric air with high CH4 concentrations is transported to the southern hemisphere through the upper troposphere (Pearman and Beardsmore, 1984;Nakazawa et al, 1991) is responsible for such a ver- April 1998 T. Saeki, T. Nakazawa, M. Tanaka and K. Higuchi 311 tical CH4 profile. On the other hand, the calculated values of the tropospheric CH4 concentration for latitudes 37-44 S decrease slightly from the surface to the middle troposphere and then increase with height.…”
Section: Vertical Profile Of the Ch4 Concentrationmentioning
confidence: 99%
“…Concerning the exchange of CO2 between troposphere and stratosphere, Nakazawa et al (1991) clearly observed a seasonal cycle of the CO2 mixing ratio, as well as the definite annual increase of the ratio, in lower-stratospheric air, both of which were caused most probably by air transport from the troposphere, as there are no major CO2 sources in the stratosphere. They considered two possibilities for this transport process, i.e., vertical diffusion of tropospheric air through the tropopause, and upwelling of tropospheric air through cumulus convection near the Intertropical Convergence Zone (ITCZ) and the South Pacific Convergence Zone (SPCZ).…”
Section: Introductionmentioning
confidence: 97%
“…The mixed air in the lower stratosphere moves through the mid-latitudes towards the North and South Poles, with velocities dependent on altitude (i.e., faster at lower altitudes), and returns to the troposphere at both poles (Nakazawa et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation